Association Between Mechanical, Physiological, and Technical Parameters With Canoe Slalom Performance: A Systematic Review - Messias, Leonardo Henrique Dalcheco; Reis, Ivan Gustavo Masselli Dos; Bielik, Viktor; Garbuio, Ana Luíza Paula; Gobatto, Claudio Alexandre; Manchado-Gobatto, Fúlvia Barros (Frontiers in Physiology, 2021)
This study aimed to systematically review studies that evaluated and compared mechanical, physiological, and technical parameters with the performance of slalom athletes. PubMed, SPORTDiscuss, and Scopus databases were searched until September 10, 2021, with no restriction of published data. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guided the study's screening and quality assessment performed by an external reviewer using a 16-checklist item. A search of the databases identified 125 studies, but only eight were eligible, including a total sample of 117 male athletes. Four reports only associated mechanical or technical parameters with the performance of the paddler. Concerning the remaining studies, only one correlated physiological data, and the others associated more than one parameter with race time. Most of the eligible reports presented significant associations between mechanical/physiological components and slalom performance. Eligible studies support that high-force development during a slalom race is a relevant parameter for performance. Aerobic metabolism is highly required during slalom tasks and is inversely associated with race time, although it may not increase the chances of winning medals. Few reports have associated canoe slalom performance with technical components, and further research should focus on this matter.